FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KUALITAS PENERAPAN AKUNTANSI PADA KOPERASI WANITA DI KECAMATAN KOTA PAMEKASAN KABUPATEN PAMEKASAN - Bahri, Syaiful (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2016)
This study aims to determine the effect of educational leadership, leadership experience, knowledge of accounting leadership, and participation in training programs on the quality of the application of accounting. Women's cooperatives show the development of good performance, most of the women's cooperative of sufficient quality even though the number of members, business volume and operating results (SHU) is not so great. The population in this study are all leaders of women's cooperatives in the district Pamekasan City. Based on the method of sampling area obtained samples of 14 women's cooperatives that have implemented the accounting records. Analysis of data using multiple linear regression.The results showed that of the four independent variables there are two variables are positive and significant impact on the quality of the application of accounting. Knowledge of accounting and the formation of the Department of Cooperatives and SMEs Pamekasan can assist business development of women's cooperatives.